A novel nondestructive testing method for amorphous Si–Sn–O films. (14th November 2016) - Liu, Xianzhe; Cai, Wei; Chen, Jianqiu; Fang, Zhiqiang; Ning, Honglong; Hu, Shiben; Tao, Ruiqiang; Zeng, Yong; Zheng, Zeke; Yao, Rihui; Xu, Miao; Wang, Lei; et al.
Abstract: Traditional methods to evaluate the quality of amorphous silicon-substituted tin oxide (a-STO) semiconductor film are destructive and time-consuming. Here, a novel non-destructive, quick, and facile method named microwave photoconductivity decay ( μ -PCD) is utilized to evaluate the quality of a-STO film for back channel etch (BCE) thin-film transistors (TFTs) by simply measuring the D value and peak reflectivity signal. Through the μ -PCD method, both optimum deposition procedure and optimal annealing temperature are attained to prepare a-STO film with superior quality. The a-STO TFTs are fabricated by the obtained optimum procedure that exhibits a mobility of 8.14 cm 2 V −1 s −1, a I on / I off ratio of 6.07  ×  10 9, a V on of -1.2 V, a steep subthreshold swing of 0.21 V/decade, a low trap density ( D t ) of 1.68  ×  10 12 eV −1 cm −2, and good stability under the positive/negative gate-bias stress. Moreover, the validity of the μ -PCD measurement for a-STO films is verified by x-ray photoelectron spectroscopy, Hall effect measurement, and the performance of STO TFTs measured by traditional methods. The non-destructive μ -PCD method sheds light on the fast optimization of the deposition procedure for amorphous oxide semiconductor films with excellent quality.